The given problem: ysqrt(1-x^2)y' -xsqrt(1-y^2)=0 is written in a form of first order "ordinary differential equation" or first order ODE.
To evaluate this, we can apply variable separable differential equation in which we express it in a form of f(y) dy= g(x) dx before using direct integration on each side.
To rearrange the problem, we move xsqrt(1-y^2) to the other to have an equation as:ysqrt(1-x^2)y' = xsqrt(1-y^2) .
Divide both sides by sqrt(1-y^2)sqrt(1-x^2) :
(ysqrt(1-x^2)y')/(sqrt(1-y^2)sqrt(1-x^2)) = (xsqrt(1-y^2))/(sqrt(1-y^2)sqrt(1-x^2))
(y*y')/sqrt(1-y^2)= x/sqrt(1-x^2)
Applying direct integration: int(y*y')/sqrt(1-y^2)= int x/sqrt(1-x^2)
Express y' as (dy)/(dx) : int(y*(dy)/(dx))/sqrt(1-y^2)= int x/sqrt(1-x^2)
Express in a form of f(y) dy= g(x) dx : int(y*dy)/sqrt(1-y^2)= int (x*dx)/sqrt(1-x^2)
To find the indefinite integral on both sides, we let:
u = 1-y^2 then du =-2y dy or (du)/(-2) =y dy
v = 1-x^2 then dv =-2x dx or (dv)/(-2) =x dx
The integral becomes:
int(y*dy)/sqrt(1-y^2)= int (x*dx)/sqrt(1-x^2)
int((du)/(-2))/sqrt(u)= int ((dv)/(-2))/sqrt(v)
Apply the basic integration property: int c*f(x) dx= c int f(x) dx .
(-1/2) int((du))/sqrt(u)= (-1/2) int (dv)/sqrt(v)
Apply the Law of Exponents: sqrt(x) = x^(1/2) and 1/x^n = x^(-n) .
Then, the integral becomes:
(-1/2) int((du))/u^(1/2)= (-1/2) int (dv)/v^(1/2)
(-1/2) int u^(-1/2)du= (-1/2) int v^(-1/2)dv
Applying Power Rule of integration: int x^ndx= x^(n+1)/(n+1)
(-1/2) int u^(-1/2)du= (-1/2) int v^(-1/2)dv
(-1/2) u^(-1/2+1)/(-1/2+1)= (-1/2) v^(-1/2+1)/(-1/2+1)+C
(-1/2) u^(1/2)/(1/2)= (-1/2) v^(1/2)/(1/2)+C
-u^(1/2)= - v^(1/2)+C
Note: (-1/2)/(1/2) = -1
In radical form: - sqrt( u)= -sqrt(v)+C
Plug-in u =1-y^2 and v=1-x^2 , we get the general solution of differential equation:
- sqrt( 1-y^2)= -sqrt(1-x^2)+C
Divide both sides by -1 , we get: sqrt( 1-y^2)= sqrt(1-x^2)+C .
Note:C/(-1) = C as arbitrary constant
For particular solution, we consider the initial condition y(0) =1 where x_0=0 and y_0=1 .
Plug-in the values, we get:
sqrt( 1-1^2)= sqrt(1-0^2)+C
sqrt(0)=sqrt(1)+C
0=1+C
C = 0-1
C =-1 .
Then plug-in C =-1 on the general solution: sqrt( 1-y^2)= sqrt(1-x^2)+C .
sqrt( 1-y^2)= sqrt(1-x^2)+(-1)
(sqrt(1-y^2))^2 =(sqrt(1-x^2) -1)^2
1-y^2= (1-x^2) -2sqrt(1-x^2) +1
Rearrange into:
y^2=-(1-x^2) +2sqrt(1-x^2)
y^2=-1+x^2 +2sqrt(1-x^2)
y^2=x^2+2sqrt(1-x^2)-1
Taking the square root on both sides:
y =sqrt(x^2+2sqrt(1-x^2) -1)
Tuesday, February 12, 2019
ysqrt(1-x^2)y' - xsqrt(1-y^2) = 0 , y(0) = 1 Find the particular solution that satisfies the initial condition
Subscribe to:
Post Comments (Atom)
Why is the fact that the Americans are helping the Russians important?
In the late author Tom Clancy’s first novel, The Hunt for Red October, the assistance rendered to the Russians by the United States is impor...
-
The poem contrasts the nighttime, imaginative world of a child with his daytime, prosaic world. In the first stanza, the child, on going to ...
-
There are a plethora of rules that Jonas and the other citizens must follow. Again, page numbers will vary given the edition of the book tha...
-
The given two points of the exponential function are (2,24) and (3,144). To determine the exponential function y=ab^x plug-in the given x an...
-
Robinson Crusoe, written by Daniel Defoe, is a novel. A novel is a genre defined as a long imaginative work of literature written in prose. ...
-
Hello! This expression is already a sum of two numbers, sin(32) and sin(54). Probably you want or express it as a product, or as an expressi...
-
The title of the book refers to its main character, Mersault. Only a very naive reader could consider that the stranger or the foreigner (an...
-
The only example of simile in "The Lottery"—and a particularly weak one at that—is when Mrs. Hutchinson taps Mrs. Delacroix on the...
No comments:
Post a Comment